EXPLORING CULINARY IDENTITY: A GASTRO-CRITICAL ANALYSIS OF AHMAD TOHARI'S RONGGENG DUKUH PARUK AND SURABANGLUS - Widya Nirmalawati; Dodi Siraj Muamar Zain; Khristianto Khristianto (Indonesian EFL Journal, 2024)
The novel Ronggeng Dukuh Paruk and the short story Surabanglus are two works by Ahmad Tohari (AT) that talk about food and how food becomes the identity of a society. RDP tells the story of how Srintil, the Ronggeng Dukuh Paruk, loses her parents due to a massive poisoning in her village caused by tempeh bongrek made by her parents. With very little knowledge of toxicology, the people of Dukuh Paruk "treat" the tempeh poisoning with empirical experience passed down from their ancestors. While Surabanglus tells the story of the friendship between Kimin and Suing which is so touching because Suing had to experience the bad luck of eating poisonous cassava due to unbearable hunger. This research is descriptive and qualitative and uses textual analysis to reveal and interpret the hidden construction in a text. The data collected is analyzed from a gastro-critical lens. Gastro-criticism is part of a critical approach to welcome the phenomenon of culinary literature in literary works. Culinary is chosen as one of the symbols, myths, and signs in the development of literary works. From the data contained in the novel RDP and short story Surabanglus in the form of narrative quotations, and dialog between characters in AT's two works, there are four findings, namely; food and its characteristics, food and socioeconomic status, food and food processing tools, food and medicine. Through these two works, AT not only presents a story with food as the plot, but at the same time, Tohari documents what and how food in a society becomes a symbol and social identity of the community.